The Effect Of Leadership In Education Administrative Learning And Knowledge On Organization Commitments Of Early Children Education Unit In Medan City - Kristianus; Benyamin; Paningkat (Publisher Cv. Inara, 2021)
Along with the transition from the New order era to the Reformation era, the central government is committed to providing regional autonomy to district and city governments to manage regional potential, including the potential for education. After the central government gave regional autonomy to district and city governments, the Medan City Government gave autonomy to the head of the Early Childhood Education unit to manage the potential of Early Childhood Education to the maximum, but in reality the management was not optimal. The purpose of this study is to find a model of organizational commitment and to determine the influence between research variables. This research method is a quantitative research method using a survey approach. The study population was 750 people and the sample of this study was 238 people with an error rate of 5%. Sampling is non-probability sampling with a purposive sampling technique based on the provisions of the sample from the population developed by Isaac and Michael. The data collection technique for this research is a questionnaire instrument using a Likert scale and a test instrument using Merriam Webster's New Collegiate Distionary technique. The results of the descriptive analysis show that 235 or 98.74% of the Educational Administrative Knowledge variable tends to be in the low category, while the other variables tend to be in the high category. Furthermore, the results of the calculation of the total direct effect show that the Educational Administrative Knowledge variable on the Organizational Commitment variable is 0.2642 or 26.42%, while the total effect of other variables is low. Furthermore, the direct and indirect proportional, sporious and unanalyzed effect caused by these three variables is 66.02% and the influence of other variables is 33.98%. Furthermore, the research results of the path coefficient test show that all the path diagram coefficients are significant. Furthermore, the results of model testing indicate that the proposed model is fit with empirical data. Therefore, based on the results of this study it is suggested that the Head of the Medan City Education Office can apply this model so that 66.02% of the organizational commitment of the head of the Children's Education unit can be maximally realized.